2008
DOI: 10.1002/yea.1583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high hydrostatic pressure on the growth and β‐carotene production of Rhodotorula glutinis

Abstract: The effects of high hydrostatic pressure (HHP) on the biomass and β-carotene biosynthesis of Rhodotorula glutinis R68 were studied. After treatment with five repeated cycles at 300 MPa for 15 min, the barotolerant mutant PR68 was obtained. After 72 h of culture, the biomass of mutant PR68 was 21.6 g/l, decreased by 8.5% compared to the parental strain R68, but its β-carotene production reached 19.4 mg/l, increased by 52.8% compared to the parental strain R68. The result of restriction fragment length polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The present study found that HHP treatment can have beneficial mutagenic effects on A. tumefaciens for CoQ10 production, which agrees with the finding of Wu et al [21] who found that the bacterial cellulose mutant M 438 was obtained after HHP treatment at 250 MPa for 15 min. Wang et al [19, 20] obtained the barotolerant mutant PR68 after five repeated cycles of HHP treatment at 300 MPa for 12 min. They found that the DNA segments of mutant PR68 were different from the original strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found that HHP treatment can have beneficial mutagenic effects on A. tumefaciens for CoQ10 production, which agrees with the finding of Wu et al [21] who found that the bacterial cellulose mutant M 438 was obtained after HHP treatment at 250 MPa for 15 min. Wang et al [19, 20] obtained the barotolerant mutant PR68 after five repeated cycles of HHP treatment at 300 MPa for 12 min. They found that the DNA segments of mutant PR68 were different from the original strain.…”
Section: Resultsmentioning
confidence: 99%
“…There were also reports that HHP treatment in laboratory could cause beneficial mutagenesis to E. coli [17, 18], R. glutinis [19, 20], and G. xylinus [21]. Compared with traditional physical and chemical mutagenesis methods, HHP treatment as a mutagen could offer some advantages such as easier handling, savings in time and money, and negligible effects to the environment [19, 20]. However, little is known related to the effectiveness of HHP treatment on improving the production of CoQ10 in microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, β-carotene was contained in the cell extracts of all four yeasts that enhanced laccase production in co-culture, and no other carotenoids were found. The four yeasts were R. mucilaginosa (Moline et al, 2012), Phaffia rhodozyma (Shi et al, 2014; Chi et al, 2015), S. pararoseus (Han et al, 2012, 2016) and R. glutinis (Wang et al, 2008; Roadjanakamolson and Suntornsuk, 2010), and have been previously reported as β-carotene-producing strains. Therefore, microbial strains that accumulate β-carotene could be the primary agent that enhances laccase production by fungi in a co-culture.…”
Section: Discussionmentioning
confidence: 96%
“…Factors such as low temperature (20°C), high air flow rate, and high hydrostatic pressure influenced positively β-carotene production by Rhodotorula sp. (Wang et al 2008;Frengova and Beshkova 2009).…”
Section: Yeastsmentioning
confidence: 97%